The Effect of Employment on Delinquent Behavior Among Youth in Hidden Situation - Chan, Gloria Hongyee (Frontiers in Psychiatry, 2019)
This study examines the effect of employment on delinquent behavior among young people in “hidden situations”. Both quantitative and qualitative methods were used, and 588 young people in these hidden situations were investigated. Results showed that some of them had employment; their employment status constituted a mediating effect on preventing them from being involved in delinquent behavior. Also, participants who had work explained the reasons for not being involved in delinquent behavior. These results reflect that whether young people in hidden situation involve in delinquent behavior depends on their employment rather than their hidden behavior itself. The implication is that practitioners should respect the youths’ self-preferred choice of employment and even advocate a revision of the definition of employment in Hong Kong.